Deepening Divides How Territorial Borders and Social Boundaries Delineate Our World - Fassin, Didier (Pluto Press, 2019)
At a glance, 'borders' and 'boundaries' may seem synonymous. But in the real (geopolitical) world, they coexist as distinct, albeit overlapping entities: the former a state's delimitation of territory; the latter the social delineation of differences. The refugee crisis in Europe showed how racial and ethnic boundaries are often instrumentalised to justify the strengthening of state borders - regardless of the cost in human life. But there are other, less tragic, examples that illustrate this overlapping as well, and ultimately demonstrate that the oft-differentiated spheres of borders and boundaries are best understood through their relationship to one another.Deepening Divides explores this relationship from many distinct perspectives and national contexts, with case studies covering five continents and drawing on anthropology, gender studies, law, political science and sociology for a truly interdisciplinary collection.